The Precursor to Glutathione (GSH), γ-Glutamylcysteine (GGC), Can Ameliorate Oxidative Damage and Neuroinflammation Induced by Aβ40 Oligomers in Human Astrocytes - Braidy, Nady; Zarka, Martin; Jugder, Bat-Erdene; Welch, Jeffrey; Jayasena, Tharusha; Chan, Daniel K. Y.; Sachdev, Perminder; Bridge, Wallace (Frontiers in Aging Neuroscience, 2019)
Soluble amyloid-β (Aβ) oligomers have been shown to induce oxidative stress, synaptic dysfunction and memory deficits which have been reported in Alzheimer's disease (AD). Administration of γ-glutamylcysteine (GGC), a precursor to glutathione (GSH) can replenish depleted GSH levels, by circumventing the regulation of GSH biosynthesis and providing the limiting substrate. In this study, we examined the effect of exogenous Aβ40 oligomers on biomarkers of apoptosis and cell death, oxidative stress, and neuroinflammation, in primary adult human astrocytes. Treatment with Aβ40 oligomers significantly reduced the cell viability and apoptosis of astrocyte brain cultures and decreased oxidative modifications of DNA, lipids, and protein after 24 hours. Co-treatment with GGC at 200µM also attenuated increased the activity of the antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) and led to significant increases in the levels of the total antioxidant capacity (TAC) and GSH and reduced the GSSG/GSH ratio. GGC also upregulated the level of the anti-inflammatory cytokine IL-10 and reduced the levels of the pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) in Oligomeric Aβ40-treated astrocytes. Our data provides renewed insight on the beneficial effects of increased GSH levels by GGC in human astrocytes, and identifies yet another potential therapeutic strategy to attenuate the cytotoxic effects of Aβ oligomers in AD.